The relation between childhood maltreatment and hedonic and eudaimonic well-being in emerging adults: A daily diary study. (April 2023) - Li, Chengcheng; Zhu, Ningzhe; Zhang, Linting; Li, Wenjie; Kong, Feng
Abstract: Background: Prior research has reported that childhood maltreatment is associated with poor well-being, but few studies have examined the association between childhood maltreatment and well-being including hedonic and eudaimonic well-being using a daily diary method. Objective: The present study investigated the association between childhood maltreatment and hedonic and eudaimonic well-being, and explored the mediating effects of social support and self-esteem. Participants and setting: Data were collected applying a 14-day daily diary method in two samples. A total of 120 Chinese emerging adults (100 female; M age = 20.48 years, age range = 18–24 years) and 229 Chinese emerging adults (187 female; M age = 20.43 years, age range = 18–27 years) comprised the discovery sample and the replication sample, respectively. Methods: Multilevel regression analysis and multilevel mediation analysis were conducted, while controlling for sex, age, and socioeconomic status. Results: In the discovery sample, the multilevel regression analysis showed that childhood maltreatment had an equal effect on predicting the two types of well-being. Additionally, the multilevel mediation analysis demonstrated that social support and self-esteem acted as independent and equally important mediators of the associations between childhood maltreatment and the two types of well-being. Moreover, the total indirect effect on the childhood maltreatment–hedonic well-being link had no significant difference from that on the childhood maltreatment–eudaimonic well-being link. The replication sample reconfirmed the results of the discovery sample, which provides greater credibility to our findings. Conclusions: Social support and self-esteem might help to improve the well-being of emerging adults who have suffered childhood maltreatment, and might therefore be important intervention targets. Highlights: Childhood maltreatment negatively predicted HWB and EWB in emerging adults. Both social support and self-esteem were independent mediators in the childhood maltreatment–well-being link. Both social support and self-esteem played equally important mediating roles in the link. Both the discovery and replication samples supported our hypotheses, which provides great credibility to our findings.